Learning beneficial worldly knowledge: between Islamic and Boko Harām perspectives - Suleiman, Hassan; Alwi, Alwi; Awang, Abdul Bari; Awang Hamat, Mohd Afandi (IIUM Press, 2024)
Islamic civilisation once led the world to develop worldly knowledge, producing significant advancements in medicine, mathematics, and astronomy. Scholars viewed these knowledge domains as complementary to religious knowledge, with the latter holding superior status. However, in recent times, some Muslim communities have distanced themselves from temporal knowledge, wrongly perceiving it as alien to Islam. Insurgent groups like Boko Harām in Northern Nigeria and neighbouring countries, including Niger, Chad, northern Cameroon, and Mali have weaponised this misconception. Boko Harām’s ideology rejects worldly education, equating it with an anti-Islamic agenda, leading to violent campaigns against educational institutions. This article addresses the misunderstanding that beneficial worldly knowledge contradicts Islamic teachings, highlighting its importance as an Islamic obligation. It explores how this misconception has contributed to violence and stagnation, such as in Boko Harām’s attacks, and analyses Islamic primary sources, the Qur’ān, the ḥadīth, and scholarly commentaries, to clarify the stance on acquiring such knowledge. The analysis includes an examination of key prophetic traditions that highlight the importance of pursuing worldly knowledge that contributes to societal welfare. The findings reveal that Islām not only permits but encourages the pursuit of beneficial worldly knowledge, which is considered farḍ kifāyah—a collective obligation upon the Muslim community. The article emphasises that education aligned with Islamic values is key to societal progress. It criticises extremist group like Boko Harām for misinterpreting Islam and calls for a return to valuing both religious and beneficial worldly knowledge to advance Muslim communities. ***** Tamadun Islam pernah memimpin dunia dalam mengembangkan ilmu duniawi dan menghasilkan kemajuan yang signifikan dalam bidang perubatan, matematik, dan astronomi. Bidang-bidang ilmu ini dianggap sebagai pelengkap kepada ilmu agama, dengan ilmu agama menduduki status yang lebih tinggi. Walau bagaimanapun, pada masa kini, terdapat beberapa Masyarakat Islam yang telah menjauhkan diri daripada ilmu duniawi, dengan salah anggap bahawa ia asing kepada Islam. Kumpulan pemberontak seperti Boko Harām di Nigeria Utara dan negara-negara jiran, termasuk Niger, Chad, utara Cameroon, dan Mali telah memperalatkan salah tanggapan ini. Ideologi Boko Harām menolak pendidikan duniawi, menyamakannya dengan agenda anti-Islam, yang membawa kepada kempen keganasan terhadap institusi pendidikan. Masalah utama adalah salah faham bahawa ilmu duniawi yang bermanfaat bertentangan dengan ajaran Islam. Artikel ini membincangkan bagaimana kepercayaan ini menyumbang kepada keganasan dan kemunduran, seperti serangan Boko Haram, dengan merujuk kepada al-Quran, ḥadīth, dan ulasan ulama untuk menjelaskan pendirian Islam tentang ilmu duniawi. Analisis ini merangkumi pemeriksaan tradisi-prophetik utama yang menekankan kepentingan mengejar ilmu duniawi yang menyumbang kepada kesejahteraan masyarakat. Penemuan menunjukkan bahawa Islam bukan sahaja membenarkan tetapi juga menggalakkan usaha untuk memperoleh ilmu duniawi yang bermanfaat, yang dianggap sebagai farḍ kifāyah — kewajipan kolektif kepada Masyarakat Iskam. Artikel ini menegaskan bahawa pendidikan duniawi yang selaras dengan nilai Islam adalah penting untuk kemajuan masyarakat. Ia mengkritik kumpulan ekstremis seperti Boko Harām kerana salah tafsir ajaran Islam dan menyeru pemulihan tradisi Islam yang menghargai ilmu agama dan duniawi untuk kemajuan masyarakat Islam.